Retorika dalam Pidato Upacara Bendera di Akun TikTok “Mommy Al” dan Pemanfaatannya sebagai Alternatif Materi Pembelajaran Teks Pidato di Kelas VIII SMP, - Dewi Wulansari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2025)
Rhetoric is the art of speaking and the ability to communicate effectively by using language as a tool. Rhetoric is one of the keys to successful speech, namely someone who speaks rhetorically is seen from the appearance of his speech. One of the key indicators of successful speech must have mastery in the use of appropriate diction, the use of effective sentences and the use of the correct language style to influence or persuade, convince, invite and persuade the interlocutor. The purpose of this study is to describe matters related to the research, namely explaining the use of diction and the use of language style in the flag ceremony speech on the Mommy Al TikTok account and the use of rhetoric in the flag ceremony speech on the Mommy Al TikTok account as an alternative learning material for speech texts in class VIII SMP. This research method uses a design and type of research, namely descriptive qualitative research. The data collection and analysis techniques use documentation techniques, namely listening techniques and note-taking techniques, and researchers use data analysis techniques with the Milles and Huberman interactive analysis model in three stages, namely data reduction, data presentation and drawing conclusions/verification. The data and data sources include two data and two data sources, namely, the first data in the form of sentences and words in the conversation delivered by the flag ceremony instructor named Erisgarini in the flag ceremony activity which leads to the formulation of the predetermined problem, the second data in the form of learning outcomes (CP) and learning objectives related to the speech text material on writing skills and speaking skills. The first data source is a video of the flag ceremony instructor's conversation by Erisgarini on Mommy Al's TikTok account which was downloaded from a laptop or cellphone, there are 11 videos in TikTok on Mommy Al's account. the second data source is the Merdeka curriculum and textbooks or Indonesian language packages for class VIII SMP. The theoretical study used is the theory of Keraf Gorys which explains the use of diction and the use of language style.
Reuploud file repositori 15 Apr 2026_Firli_Tata
Keywords: Rhetoric; Diction; Speech Text Learning; TikTok